A 1, 3, 2‐Diazaphospholene‐Catalyzed Reductive Claisen Rearrangement. (16th May 2019) - Reed, John H.; Donets, Pavel A.; Miaskiewicz, Solène; Cramer, Nicolai
Abstract: 1, 3, 2‐Diazaphospholenes (DAPs) are an emerging class of organic hydrides. In this work, we exploited them as efficient catalysts for very mild reductive Claisen rearrangements. The method is tolerant towards a wide variety of functional groups and operates at ambient temperature. Besides being enantiospecific for substrates with existing stereogenic centers, the diastereoselectivity can be switched by varying solvents and DAP catalysts. The reaction kinetics show direct rearrangements of O‐bound phospholene enolates and provide a proof‐of‐principle for catalytic enantioselective reactions. Abstract : Umgelagert mit DAP : 1, 3, 2‐Diazaphospholene (DAPs) sind effiziente Katalysatoren für reduktive Claisen‐Umlagerungen bei Raumtemperatur. Die Methode toleriert eine Vielzahl an funktionellen Gruppen und ist für Substrate mit stereogenen Zentren enantiospezifisch. Die Diastereoselektivität kann durch die Wahl des Lösungsmittels und DAP‐Katalysators kontrolliert werden.